Chimbutane, Feliciano 2011. Rethinking Bilingual Education in Postcolonial Contexts. N. H. Hornberger and C. Baker ed Bristol, Buffalo, Toronto: Multilingual Matters. 183p. - (:unkn) unknown (My University, 2012)
Some historical shortcomings re aspects of assimilation in Chimbutane's recent book on bilingual education in Mozambique
Keywords: African Research